Prunella vulgaris L. – A Review of its Ethnopharmacology, Phytochemistry, Quality Control and Pharmacological Effects - Pan, Junying; Wang, Haoyu; Chen, Yinghua (Frontiers in Pharmacology, 2022)
Prunella vulgaris L. (PVL) is dried fruit spike of Lamiacea plant Prunella vulgaris L., which is a perennial herb with medicinal and edible homology used for thousands of years. PVL is bitter, acrid, cold, and belongs to the liver and gallbladder meridians. It clears the liver and dissipate fire, improve vision, disperse swelling, and has satisfactory clinical therapeutic effects on many diseases such as photophobia, dizziness, scrofula, goiter, breast cancer. The collection of information and data related to PVL comes from literatures retrieved and collated from various online scientific databases (such as CNKI, VIP, PubMed, Web of Science, ResearchGate, Science Database), ancient books of traditional chinese medicine (Encyclopedia of Traditional Chinese Medicine, Classics of Traditional Chinese Medicine, Dictionary of Traditional Chinese Medicine), and Doctoral and Master’s Dissertations. Currently, the major chemical constituents isolated and identified from PVL are triterpenoids, steroids, flavonoids, phenylpropanoids, organic acids, volatile oils and polysaccharides. Modern pharmacological studies have shown that PVL has a wide range of pharmacological activities, including anti-inflammatory, anti-tumor, antibacterial and antiviral effects, as well as immune regulation, antihypertensive, hypoglycemic, lipid-lowering, antioxidant, free radical scavenging, liver protection, sedative and hypnotic effects. This paper reviewes the botany, ethnopharmacology, traditional application, phytochemistry, analytical methods, quality control, pharmacological effects of PVL. It can be used not only as medicine, but also gradually integrated into the “medicine and food homology” and “Chinese medicine health” boom. More importantly, it has great potential for drug resources development. This paper deeply discusses the shortcomings of current PVL research, and proposes corresponding solutions, in order to find a breakthrough point for PVL research in the future. At the same time, it is necessary to further strengthen the research on its medicinal chemistry, mechanism of action and clinical application efficacy in the future, and strive to extract, purify and synthesize effective components with high efficiency and low toxicity, so as to improve the safety and rationality of clinical medication.